2016
DOI: 10.26687/archnet-ijar.v10i1.824
|View full text |Cite
|
Sign up to set email alerts
|

Research Utilization in the Design Decision Making Process

Abstract: This article summarizes findings from a national survey of interior design practitioners in the United States (N=366

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 10 publications
(31 citation statements)
references
References 27 publications
1
30
0
Order By: Relevance
“…Numerous textbooks are offered on the subject, and there are now entire academic programs focused on the generation and application of design research. In my aforementioned survey, interior designers did indicate a growing awareness and overall value placed on design research pursuits (Huber, ). Some of these same participants noted the willingness of some of their clients to pay for research services.…”
Section: On the Right Trackmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous textbooks are offered on the subject, and there are now entire academic programs focused on the generation and application of design research. In my aforementioned survey, interior designers did indicate a growing awareness and overall value placed on design research pursuits (Huber, ). Some of these same participants noted the willingness of some of their clients to pay for research services.…”
Section: On the Right Trackmentioning
confidence: 99%
“…Thus, the initial topic selection plays a vital role in framing the study's subsequent findings. Moreover, in my studies situated within interior design, practitioners cited perceptions of research topics as “too vague, limited, or ‘overly academic’ in nature” (Huber, , p. 14). The difficulty lies in balancing rigor and relevance (Panda and Gupta, ) because rigorous studies can take years to complete and may lose relevance before their publication.…”
Section: Lessons From Economicsmentioning
confidence: 99%
“…Findings suggested that greater elaboration resulted when messages were presented in a visually integrative manner (i.e., graphics with text) and that visual cues could be, and often are, processed as central elements. In fact, previous research by the author suggested that hedonic qualities including composition and use of imagery may attract interior design practitioners to information sources (Huber, ).…”
Section: Contextmentioning
confidence: 99%
“…In fact, in a recent survey by the author, over half of the 366 interior design practitioner respondents indicated that they generally spent less than 10 minutes reviewing an information source. Moreover, only 11% referenced scholarly articles (Huber, ). With a myriad of information sources available and little time with which designers can assess them, it may behoove design scholars to employ tactics rooted in communication design and persuasive messaging, thus persuading designers to read the material and potentially apply the research findings despite any stressors at hand.…”
Section: Introductionmentioning
confidence: 99%
“…While literature lacks recent studies exploring the decision‐making processes of designers when making human capital decisions, studies have suggested that designers call on rapid information processes during the design process (Gray, Seifert, Yilmaz, Daly, & Gonzalez, ; Yilmaz & Seifert, ) and when reviewing information under time constraints (Huber, , , ). Given that over one in four of Huber and Pable's () hiring practitioner respondents received over 50 applicants for a typical entry‐level interior design job opening, one might infer that the time allocated to each candidate's package is relatively limited, and consequently, heuristics may factor heavily into these initial assessments.…”
Section: Literaturementioning
confidence: 99%